(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
This paper takes into consideration a peripheral part of the E Area in Nora, situated near the southwestern limit of the Central Baths, sheding light on a structure pertaining to a great construction, partially destroyed by the thermal building. The article shows the results of the latest campaign (2012), which tried to supply a systematic documentation of a small area, dug only in the ‘50s; it also tries to express some hypothetical considerations about the function and the stratigraphical position of this structure.